Cholecystectomy under thoracic epidural anaesthesia for patient with severe intra‐pulmonary shunt - Frankel, Agustina (Respirol Case Rep, 2020)
Pulmonary arteriovenous malformations are common in patients with hereditary haemorrhagic telangiectasia and can be associated with significant hypoxia and intra‐pulmonary shunt. We present a case of a young man with a known 57% calculated shunt requiring abdominal surgery and the multidisciplinary decisions required in the preoperative period to minimize post‐operative complications.